Alimentación de alevinos de Colossoma macropomum (Cuvier,1816) “gamitana” utilizando larvas de Hermetia illucens "mosca soldado” y termitas en la Amazonía Peruana - Najar Reategui, Jorge (2024)
This work was carried out at the Fernando Alcántara Bocanegra Research Center (CIFAB) of the Peruvian Amazon Research Institute (IIAP) during the months of June to September 2022. The objective was to determine the variation in the growth of Colossoma macropomum “gamitana” fry fed with larvae of Hermetia illucens “black soldier fly” and termites. A total number of 180 C. macropomum fry with initial sizes between 3-4 cm and weighing 1.5 to 2 g were used. Sixty fry per treatment were distributed in 9 floating cages. T1: fry fed with larvae of H. illucens “black soldier fly”, T2: fry fed with termites and a control treatment T0: fry fed with balanced feed. The larvae of H. illucens “black soldier fly” were produced in handmade modules at CIFAB-IIAP using orange waste as substrate. The termites were collected from forested areas of CIFAB-IIAP. The results of the study showed that C. macropomum fry fed with black soldier fly larvae (T1) presented higher growth and weight gain, as well as better results in zootechnical indexes compared to fish fed with termites (T2). It is concluded that fish fed with H. illucens larvae are more suitable for feeding C. macropomum fry than the use of termites.